Rice straw supply chain for electricity generation in Malaysia: Economical and environmental assessment - Shafie, S.M.; Masjuki, Haji Hassan; Mahlia, Teuku Meurah Indra (Elsevier, 2014)
Rice straw supply costs were estimated and the supply potential was analyzed to determine the optimum amount of recourses and rice straw power plants. The logistic cost consists of rice straw collection, transportation to collection centre, collection centre cost and transportation to power plant. The total logistic cost, ready at power plant is found to be between RM 39.95 per bale and RM 65.80 per bale. The carbon emission and the environmental impact are analyzed throughout the life cycle involved in each process. Life cycle emission of logistic system is between 0.0234 t CO2-Eq +/- 0.11 percent per bale, ready at 10 MW power plants. Climate change has a significant impact on environment compared to other parameters like toxicity and acidification. For a small power plant having a capacity of less than 10 MW, the number of collection centres is not significant with respect to the total transportation cost parameter. (C) 2014 Elsevier Ltd. All rights reserved.